(untitled) (Global Journal of Medical Research, 2018)
Introduction: There is a high prevalence of low serum testosterone in type 2 diabetes mellitus patients. In this study, we tried to determine the level of serum testosterone in type 2 diabetes mellitus patients. Methods: A total of 241 patients were taken in the study. Out of this, 121 patients had type 2 diabetes mellitus and 120 were normal. For diagnosis of diabetes HbA1c level of ≥ 6.5 was taken. Serum testosterone levels were measured in all the participants. Results: The mean age of the participants was 46.95 ± 6.89 in diabetic patients and 45.86 ± 5.45 in the controls. The mean serum testosterone levels in the diabetes population was 312 ± 14.6 ng/dl and in the control population was 678 ± 17.5ng/dl. On applying chi square test, the p value was calculated to be 0.02. This shows the difference is statistically significant. Conclusion: Type 2 diabetes mellitus is associated with low levels of serum testosterone levels.